Negro Employment in Finance : a Study of Racial Policies in Banking and Insurance - Thieblot, Jr., Armand J. (Anniversary Collection., 2017)
Founded in 1921 as a separate Wharton department, the Industrial Research Unit has a long record of publication and research in the labor market, productivity, union relations, and business report fields. Major Industrial Research Unit studies as published as research projects are completed. This volume is Study no. 47.